Sosialisasi Strategi Pengembangan Umkm Melalui Digital Marketing Kelurahan Turi Kota Blitar - Putri Indah Rachmawati; Nanik Hariyana (Cv. Utility Project Solution, 2023)
Wide acces to digital channels for businesses today makes it easier for users to maximize the features provided. For example, on social media, which already has ecommerce features and advertising features. The benefits of social media marketing that is done properly can save on higher advertising and transaction costs because a wider reach makes sales opportunies higher. However, not all business people can carry out digital marketing in the right way due to a lack of understanding about digital marketing. This mentoring activity aims to help increase the understanding of MSMEs actors in the Turi Village regarding digital marketing. The socialization activity with the theme “Socialization of MSME Development Strategies Through Digital Marketing” is one of the efforts to increase understanding of the topics being socialized. The methods carried out online and offline are conducting surveys, mapping, socializing, collect responses through questionnaires, and mentoring. The socialization activity had an impact on the perpetrators of UMKM in the Turi Village, totaling 25 participants, as evidenced by the decrease in the